Characterization and biodegradation rate of hydroxyapatite/shellac/sorghum for bone scaffold materials. Issue 1 (1st January 2021) - Triyono, Joko; Adityawan, Rizky; Dananjaya, Platino; Smaradhana, Dharu Feby; Masykur, Abu
Abstract: This study aims to fabricate bio-composites of hydroxyapatite/shellac/sorghum as bone scaffold material in biomedical applications. Hydroxyapatite is made from bovine bone powder, while shellac is the end product from processing lice with adhesive properties, which are biodegradable and non-toxic. Furthermore, sorghum was used as a pore-forming material. The production of the materials was carried out using dry method which was sintered at a temperature of 1000°C. Subsequently, characterization of the bio-composites was carried out through X-Ray Diffraction, Scanning Electron Microscopy and Fourier Transform Infrared. The results of hardness and compression test were compared using pure hydroxyapatite and human bone as gold standard material. Furthermore, the biodegradation rate of these materials was also reported.